Topical Problems of Choral and Orchestra Conductors Training in the Russian Far East Region - N. F. Semenova (Высшее образование в России)
The article covers a wide range of problems connected with choral and orchestra conductors training in the Russian Far East Region. The author focuses on the specificity of the educational process organization for choral and orchestra conductors. The formation of orchestra and choral conductor’s professional skills is a three-dimensional process including educational work, concert-performing and research work. The author describes an experience of Khabarovsk State Institute of Culture in training professionals in choral and orchestra performance. The article describes the content, methodical and didactic aspects of the educational process of students majoring in Conducting. The author dwells on the features of the organization of students’ creative work and ways of cooperation between the Institute and the representatives of the creative and artistic environment.